f(x), где х - переменная.
f(1), 1 заменяет х, значит если вместо 1 будет g(x), то нам надо подставить вместо х функцию:
f(x) = 1/(1-x)
g(x) = 1/(x+1)
f(g(x)) = f(1/(x+1)) = (1 - 1/(x+1))^-1 = ((x+1-1)/(x+1))^-1 = (x/(x+1))^-1 = (x+1)/x
g(f(x)) = g(1/(1-x)) = (1/(1-x) + 1)^-1 = (-1/(x-1)+1)^-1, функции уже не равны.
(-1/(x-1)+1)^-1 = ((x-1-1)/(x-1))^-1 = (x-1)/(x-2)
1) f(g(x)) = (x+1)/x
g(f(x)) = (x-1)/(x-2)
2) неверно
f(x), где х - переменная.
f(1), 1 заменяет х, значит если вместо 1 будет g(x), то нам надо подставить вместо х функцию:
f(x) = 1/(1-x)
g(x) = 1/(x+1)
f(g(x)) = f(1/(x+1)) = (1 - 1/(x+1))^-1 = ((x+1-1)/(x+1))^-1 = (x/(x+1))^-1 = (x+1)/x
g(f(x)) = g(1/(1-x)) = (1/(1-x) + 1)^-1 = (-1/(x-1)+1)^-1, функции уже не равны.
(-1/(x-1)+1)^-1 = ((x-1-1)/(x-1))^-1 = (x-1)/(x-2)
1) f(g(x)) = (x+1)/x
g(f(x)) = (x-1)/(x-2)
2) неверно